1967
DOI: 10.1002/pol.1967.160050402
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic poly(amic acids): Fundamental structural studies

Abstract: SynopsisAromatic poly(amic acids) derived from pyromellitic dianhydride and 4,4',-diaminodiphenyl ether were characterized by dilute solution techniques. Number-average molecular weights a,, of 13 samples ranged from 13,000 to 55,000 (DP 31-131). Weight-average molecular weights aw of 21 samples ranged from 9,900 to 266,000. The ratio &fw/&f,, was between 2.2 and 4.8. Heterogeneous polymerization yielded higher molecular weight polymer than homogeneous polymerization. The molecular weight could be varied syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…As shown in Fig. 2, the intrinsic viscosity of PAA decreases as the milling time increases, slightly at first and then rapidly from 2.61 dL/g to 0.66 dL/g within a milling time of 18 h, corresponding to a large reduction in the viscosity-average molecular weight of PAA from 1.54 Â 10 5 to 2.76 Â 10 4 [18]. It seems that the PAA remains stable within 2 h of ball milling time, and the reduction of viscosity becomes level off if the milling time is higher than 12 h. The significant reduction in the PAA molecular weight should result from the high shearing force and the friction induced temperature rise environment.…”
Section: Direct Dispersion In Paamentioning
confidence: 91%
“…As shown in Fig. 2, the intrinsic viscosity of PAA decreases as the milling time increases, slightly at first and then rapidly from 2.61 dL/g to 0.66 dL/g within a milling time of 18 h, corresponding to a large reduction in the viscosity-average molecular weight of PAA from 1.54 Â 10 5 to 2.76 Â 10 4 [18]. It seems that the PAA remains stable within 2 h of ball milling time, and the reduction of viscosity becomes level off if the milling time is higher than 12 h. The significant reduction in the PAA molecular weight should result from the high shearing force and the friction induced temperature rise environment.…”
Section: Direct Dispersion In Paamentioning
confidence: 91%
“…11 A Varian Unity Inova 500 spectrometer was used to obtain 1 H NMR spectra. Poly(amic acid) solutions were dissolved in deuterated dimethylsulphoxide (DMSO-d 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…The weight average molecular weight of the PAA samples is believed to be of the order of 100,000 to 250,000 (1). Studies of similar aromatic PAA showed M,, in the range 13,000 to 55,000 M , in the range 9,900 to 266,000, and the Mark-Houwink relation given by [q] = 1.85 x 10-4 M,O.W (9,10).…”
Section: Methodsmentioning
confidence: 99%